Testing the Model of Goal-Directed Behavior for Predicting Binge Drinking Among Young People. (21st March 2017) - Gabbiadini, Alessandro; Cristini, Francesca; Scacchi, Luca; Monaci, Maria Grazia
ABSTRACT: Background: One of the most problematic modes of alcohol consumption in young adults is risky drinking in single episodes, which typically takes place in social contexts. Several studies have applied the Theory of Planned Behavior to drinking intentions and behavior in young people. However, previous studies show that this model lacks a "bridge" that links a mental process like intentions to a physical process represented by the actual action. Objectives: The aim of the present study is to test the predictive power of the Model of Goal-Directed Behavior plus social influences in order to overcome theory of planned behavior gaps in predicting binge-drinking behavior in young people. Methods: 404 undergraduates completed a questionnaire containing measures for the MGB variables, social identity, and group norms. Two weeks later, participants reported how many times they had had five/four or more alcoholic drinks on a single occasion. Structural equation modeling revealed strong support for model validity. Results: The final equation accounted for 66% in intentions to binge drink, and 48% in drinking behavior, while a planned behavior model accounted for the 47% of variance in intentions to binge and 37% of the drinking behavior. Social influences positively affected desire and intentions to drink. Conclusions: Our findings suggest that, compared to other attitude-behavior frameworks, the MGB is preferable in modeling the proximal determinants of binge drinking. Therefore, the distinction between desire and intention and the consideration of social influences seem to be essential to improve the prediction of binge drinking among young people.